A study of cardio-pulmonary efficiency in different categories of runners - Dasgupta, P. K.; Mukhopadhyay, A. K.; De, A. K. (Indian Journal of Physiology and Pharmacology, 2000)
Selected short distance runners, middle distance runners and long distance runners were subjected to graded exercise on a treadmill. The maximum aerobic power (VO2 max) and other indices related to oxygen transport system viz. heart rate, ventilation volume, breathing reserve, dyspnoeic index, O2 pulse and RQ were recorded at respective VO2 max work loads, and the values were compared. Long distance runners and middle distance runners showed a significantly higher VO2 max than the short distance runners when VO2 max was expressed per unit of body weight. Among the endurance runners, long distance runners had a significantly lower resting pulse rate as well as the maximum heart rate during work than the middle distance runners. On comparison, Ventilation Volume, Breathing reserve, Dyspnoeic index, O2 pulse and RQ at VO2 max work loads do not differ significantly among different categories of runners.